A Case Series of Intractable Urologic Pain Relieved by Punctate Midline Myelotomy: Should the Procedure's Indications be Expanded?. (16th November 2020) - Ball, Tyler; Aljuboori, Zaid; Adams, Shawn W; Nauta, Haring J.W
Abstract: INTRODUCTION: The post synaptic dorsal column pathway (PSDC) is a major pathway responsible for visceral pain transmission that has been selectively interrupted to treat malignant pain in the past and benign gastrointestinal pain more recently, raising the question of its efficacy for other visceral pain syndromes. METHODS: Three patients with refractory pain felt to be related to ureteral stones or ureteral surgery were offered a Punctate Midline Myelotomy (PMM). Patients were not candidates or had failed other available medical and surgical options. PMM by laminectomy at T7 was performed. The midline of the spinal cord was determined using anatomic landmarks and confirmed using dorsal column mapping. An approximately 1.5 mm wide transverse crush injury centered on the midline was made to a depth of approximately 5mm (4 mm in one subject with an abnormally flattened spinal cord). RESULTS: All patients had substantial pain relief starting in the immediate post-operative period. One patient had a return of her groin pain nearly 5 months following the procedure, although the perineal pain with urination has not returned. All patients had normal gait and station and normal strength post-operatively. All patients reported mild post-operative numbness and/ or tingling, which involved the soles of the feet in one patient and the medial aspect of one lower extremity in two other patients. Proprioception and vibratory sensation were intact in these patients, and there were no alterations to bowel or bladder function. CONCLUSION: The return of much of the pain in one patient, as well as the invasive nature of PMM, should caution against its indiscriminate use until all other options have been exhausted. However, for patients in this category, preliminary data suggest PMM may be effective for visceral pain of urologic origin. More clinical experience is needed before claims of its durability for urologic pain are made.